Building a more robust U.S.-Philippines alliance - Hiebert, Murray; Nguyen, Phuong (Research Associate with the Sumitro Chair for Southeast Studies at CSIS); Poling, Gregory B. (Center for Strategic & International Studies ; Lanham ; Boulder ; New York ; London : Rowman & Littlefield, 2015)
"With elections in both the Philippines and the United States in 2016, the future of the alliance must be institutionalized to ensure that it is not diminished by a change of leadership in either country. A new Enhanced Defense Cooperation Agreement and cooperation in the South China Sea are important components of the new era of relations, but they are not and should not be the only defining features of the alliance. Given the long history of U.S.-Philippine relations, the alliance must be based on more robust cooperation across the spectrum of political, security, economic, and sociocultural relations. Security concerns provide an acute impetus for leaders to put more energy into the relationship, but its sustainability will require a more comprehensive focus"--Publisher's web site.